Analysis of Farmer Household Food Security in Sedenganmijen Village, Krian District, Sidoarjo Regency - Amalia, Hania Putri; Hendrarini, Hamidah; Syah, Mirza Andrian (Trunojoyo University of Madura, 2025)
Food security in a region can be measured from food availability, purchasing power, and consumption level of the population. The study aims to determine household expenditure priorities by analyzing consumption patterns and the level of resilience of farmer households as a form of prevention or handling of food insecurity problems. So a quantity analysis with Daily Value (RDA) and quality analysis with Food Hope Pattern (PPH). The study site was taken purposively. Sedenganmijen Village makes agricultural workers as its main and side livelihood. The sampling method uses saturated sampling (census). The sample selected in this study was 35 farmworker households through a food recall questionnaire within a week. The results of the study explained that the level of resilience in Sedenganmijen Village of 334.93% can be said to be food secure with a food security level exceeding 91-110% AKE. Meanwhile, the diversity of household consumption patterns with a PPH Score of 88.27 where the figure is still less than the provisions of the Normative Income Tax Score, which is 100. So it needs to be done to increase knowledge on the consumption of nutritious, diverse, balanced, and safe food (B2SA).